2013
DOI: 10.3389/fpsyg.2013.00561
|View full text |Cite
|
Sign up to set email alerts
|

German and Korean mothers' sensitivity and related parenting beliefs

Abstract: This study contributes to a differentiated understanding of maternal sensitivity in cultural and situational context. We investigated differences and similarities in German and Korean mothers' maternal sensitivity. We interviewed 92 German and 100 Korean mothers of first graders about their preference for proactive (anticipating children's needs) or reactive sensitivity (responding to children's direct cues) in different scenarios. Related parenting beliefs were assessed by asking the mothers to explain the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 28 publications
0
14
1
Order By: Relevance
“…This result differs from previous findings with German-speaking population (Niklas and Schneider, 2013;Niklas et al, 2015). Given our results showing that parents' teaching was less frequent in German than in all other languages (see Table 1), one possible interpretation would be that German-speaking Austrian parents may follow a low involvement strategy, possibly because they value their child's autonomy (Ziehm et al, 2013) and rarely think their child needs much help in learning to read and spell before the beginning of Grade 1. Contrary to our expectation, the strongest association between parent teaching and letter knowledge was found in Greek, not in English.…”
Section: Discussioncontrasting
confidence: 99%
“…This result differs from previous findings with German-speaking population (Niklas and Schneider, 2013;Niklas et al, 2015). Given our results showing that parents' teaching was less frequent in German than in all other languages (see Table 1), one possible interpretation would be that German-speaking Austrian parents may follow a low involvement strategy, possibly because they value their child's autonomy (Ziehm et al, 2013) and rarely think their child needs much help in learning to read and spell before the beginning of Grade 1. Contrary to our expectation, the strongest association between parent teaching and letter knowledge was found in Greek, not in English.…”
Section: Discussioncontrasting
confidence: 99%
“…For the current analysis, one scenario was excluded because it asks about the belief on children's role rather than mothers' role. During the interview, mothers were asked about how a mother should behave in each scenario (see also Ziehm et al, 2013). An example scenario is, "The child probably stumbled over a stone but s/he is not crying."…”
Section: Methodsmentioning
confidence: 99%
“…Recent Korean studies have reported that intimate parent-child relationship facilitated children's motivation and ability for regulating their own behaviors (Jang & Jang, 2012;Park, Kim, Shin, & Lee, 2014). Also, Ziehm, Trommsdorff, Heikamp, and Park (2013) found that Korean mothers who endorsed proactive sensitivity believed that this could help their children to cope with negative emotions, whereas, in Germany (i.e., a culture where individualistic values are dominant), mothers preferred the use of reactive sensitivity for encouraging their children's independence. In another study on teachers' socialization beliefs, Rothbaum et al (2006) found that, in Japan (i.e., a culture where interdependence is emphasized), teachers preferred to be proactively sensitive by anticipating children's needs in order to promote children's teacher reliance.…”
Section: Maternal Sensitivity To Child Needsmentioning
confidence: 99%
“…They provide nutrition and shelter, and they care for them when they are ill, injured, or stressed. Although there are cultural variations in the degree to which parents act to anticipate and avoid children's stress or, instead, wait and help them if distressed (Ziehm, Trommsdorff, Heikamp, & Park, 2013), parents seek to protect their children from distress. Their protective behaviors contribute to their children's sense of security, i.e., their development of attachment (Bowlby, 1969;George & Solomon, 2008).…”
Section: Competent Parenting Is Protectivementioning
confidence: 99%